Avian Mycobacteriosis: Still Existing Threat to Humans - Slany, Michal; Ulmann, Vit; Slana, Iva (BioMed research international, 2016)
The nontuberculous mycobacteria are typically environmental organisms residing in soil and water. These microorganisms can cause a wide range of clinical diseases; pulmonary disease is most frequent, followed by lymphadenitis in children, skin and soft tissue disease, and rare extra pulmonary or disseminated infections. Mycobacterium avium complex is the second most common cause of pulmonary mycobacterioses after M. tuberculosis. This review covers the clinical and laboratory diagnosis of infection caused by the members of this complex and particularities for the treatment of different disease types and patient populations.
Keywords: mikrobiologie životního prostředí; Humans; Mycobacterium avium komplex; Mycobacterium avium Complex; Mycobacterium avium-intracellulare Infection; zdroje nemoci; rizikové faktory; Environmental Microbiology; Disease Reservoirs; Risk Factors; zvířata; intracelulární infekce bakterií Mycobacterium avium; Animals; lidé